2020
DOI: 10.1007/s00330-020-07174-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing acquisition-related radiomics variability by image resampling and batch effect correction to allow for large-scale data analysis

Abstract: Objective To identify CT-acquisition parameters accounting for radiomics variability and to develop a post-acquisition CT-image correction method to reduce variability and improve radiomics classification in both phantom and clinical applications. Methods CT-acquisition protocols were prospectively tested in a phantom. The multi-centric retrospective clinical study included CT scans of patients with colorectal/renal cancer liver metastases. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 25 publications
3
97
0
Order By: Relevance
“…The in-house developed pipeline started first by applying bias field correction to every image using MIM software (version 6.9.4, Cleveland, OH, USA) to correct for nonuniform grayscale intensities in the MRI caused by field inhomogeneities. Second, in order to minimize acquisition-related radiomics variability, voxel dimensions were standardized across the cohorts to arrive at an isotropic voxel resolution of 1 mm3 by means of cubic interpolation [ 37 ]. Third, to homogenize arbitrary MRI units and clip image intensities to a certain range, a histogram matching technique was applied, adjusting the pixel values of the MR image such that its histogram matched that of the target MR image from the training data cohort [ 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The in-house developed pipeline started first by applying bias field correction to every image using MIM software (version 6.9.4, Cleveland, OH, USA) to correct for nonuniform grayscale intensities in the MRI caused by field inhomogeneities. Second, in order to minimize acquisition-related radiomics variability, voxel dimensions were standardized across the cohorts to arrive at an isotropic voxel resolution of 1 mm3 by means of cubic interpolation [ 37 ]. Third, to homogenize arbitrary MRI units and clip image intensities to a certain range, a histogram matching technique was applied, adjusting the pixel values of the MR image such that its histogram matched that of the target MR image from the training data cohort [ 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CT images in arterial and venous phases were firstly resampled isotropically into 1 mm ×1 mm × 1 mm voxel size by using trilinear interpolation, to reduce the heterogeneity resulted from different scanner (24,25). Then the CT images in respective phases were sequentially imported into A.K.…”
Section: Image Process and Lesion Roi Segmentationmentioning
confidence: 99%
“…Considering the radiomics feature could be extracted from the single cross section (two dimensional, 2D) or multi-slices (three dimensional, 3D) of the tumor in CT images, the reported radiomics-based pancreatic cancer studies have either applied 2D segmentation (20) or 3D whole-tumor segmentation (14,(21)(22)(23)(24)(25). However, whether to select 2D regions of interest (ROIs) or 3D ROIs still remains unclear for invasive behavior prediction in pSPN.…”
Section: Introductionmentioning
confidence: 99%
“…These sources of variation are further referred to as batch effects. ComBat was subsequently adopted in radiomics analysis, and some studies reported that ComBat outperforms other harmonization methods (e.g, histogram-matching, voxel size normalization, and singular value decomposition) in radiomics analyses [15,16]. Several radiomics studies have reported on the successful application of ComBat in removing the differences in RFs introduced by different vendors and acquisition protocols [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%